THE GOVERNMENT GOODS AND SERVICES PROCUREMENT IN THE 5.0’S SOCIETY ERA: SHARIA ECONOMIC LAW PERSPECTIVE - Bangun, Revanda; Arifin, Muhammad; Nadirah, Ida (Proceeding International Seminar of Islamic Studies, 2023)
This study aim to analyzing the government goods and services procurement in the 5.0’s society with Sharia economic law perspective. This research used normative juridical method based secondary data. Data analyzed by qualitative analysis methods. The results of the study conclude that Presidential Regulation Number 16 of 2018, LKPP Regulation Number 11 of 2018 and Presidential Regulation Number 17 of 2023 as a constitutional basis for adaptation the 5.0. Society Era in the government goods and services procurement was accordance with the Al-Qur'an, Al-Hadith, and the mu'amalah principles which include: The Law of Origin in Muamalah is Mubah (permissible), realizing Benefit, eliminating Competitive Prices, Eliminating Unethical Interventions Prohibited, Avoiding Exploitation, Honest and Trustful. Apart from that, it is also in accordance with Sharia Economic Law which contains the ikhtiyari principle (voluntary); trustworthiness (keep promises); Luzum principle (unchanged); the mutual benefit principle; taswiyah principle (equality); transparency principle; ability principle; taysir principle (convenience); the good faith principle; lawful cause; the al-Hurriyah principle (freedom to contract), but still does not consider the principle of ikhtiyati (prudence).